IS KUWAIT TV DIGLOSSIC? A SOCIOLINGUISTIC INVESTIGATION - Abdulmohsen Dashti; Fatima Dashti (European Scientific Journal, ESJ, 2015)
Diglossia is a sociolinguistic term refers to the use of two varieties of one language in a given community; one is regarded as the high variety and the other as a low variety. This paper is a qualitative study thatinvestigates diglossia in various Kuwaiti TV stations. It attempts to mainly see if the two varieties are used differently whenever there is a change of topic in TV programs. Topics investigated include news, programs discussing political issues, cooking, sports, religion, and fashion. The researchers made sure that all programs chosen for investigation are presented by Kuwaitis. Data collected for this study relied mainly on observations and videotaping which took five months duration. Data was then phonetically transcribed and qualitatively analyzed.Speech extracts indicating the use of either H or L variety are demonstrated where necessary. The analysis showed that diglossia extensively exists in all the Kuwaiti TVchannels under investigation. Such a study may, to some extent, draw some generalizations about diglossia in Kuwait due to the fact that these channels present a variety of diglossic behaviors in different settings by different Kuwaiti speakers.